Аналіз суспільного життя крізь призму уявлень М. Фуко : від "археології знання" до "генеалогії влади" - Капустіна, Надія Борисівна; Капустина, Надежда Борисовна; Kapustina, N. (My University, 2010)
The analysis of modern society, conducted in this article, is based on the works of famous French philosopher Michel Foucault. Among the problems of modern society, affected by Foucault the following problem stands – connection between knowledge and power, change of mechanisms of functioning of power in modern societies. Research is guided by the method of archaeology offered by the philosopher. This method allows to expose the structure of thought, determining the scopes of conceptions of certain epoch.
Капустіна Н. Б. Аналіз суспільного життя крізь призму уявлень М. Фуко : від "археології знання" до "генеалогії влади" / Н. Б. Капустіна // Актуальні проблеми політики : зб. наук. пр. / редкол. : С. В. Ківалов (голов. ред.), Л. І. Кормич (заст. голов. ред.), Ю. П. Аленін [та ін.] ; МОНмолодьспорт України, НУ ОЮА. - Одеса : Фенікс, 2010. - Вип. 40. - С. 426-435.
Keywords: філософія права; М. Фуко, його філософські погляди на право; аналіз суспільного життя; "археологія знання"; "генеалогія влади"; философия права; М. Фуко, его философские взгляды на право; анализ общественной жизни; "археология знаний"; "гениалогия власти"; philosophy of law; Foucault, his philosophical views on the right; Analysis of public life; "archeology of knowledge"; "genialogiya power"